Pedagogical Conditions of Forming Children’s Evaluative Attitude toward the Nature in the Conditions of Educational Space Aestheticization - Abramovych, Galyna; Siginyshyna, Galyna (Pedagogical Discourse, 2013)
Pedagogical conditions of forming children’s evaluative attitude toward the nature, initial representations abaut its aesthetic value are determined in the article. Forming children’s evaluative attitude toward the nature is presented in a defenite algorithmic. The certain standards which the children of preschool age need to learn during their touch the environment are accentuated. The meaning of concept «Emotions Alphabet» is submited and the adults role at its learning by the children is accentuated. Besides the effective ways for activation of forming children’s evaluative attitude toward the nature are noticed. The using of national nature learning traditions at the kindergartens is accented.